Rozvoj franchisingové sítě - Petrová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Tato diplomová práce je zaměřena na zhodnocení rozvoje franchisingové sítě COMFOR, pohybující se na trhu informačních a komunikačních technologií. Jsou v ní zpracovány teoretická východiska pro uplatnění franchisingu v praxi, analýza firmy a jejího okolí, strategie rozvoje franchisingového konceptu a jednotlivé části implementace konceptu.

This thesis is focused on the evaluation of the franchising network COMFOR development. COMFOR is present on the information and communication technologies market. My thesis contains the theoretical ground for franchising use in practice, company analysis and analysis of its neighbourhood, development strategy of franchising draft and single parts of the draft implementation.
The Development of Franchising Network
Keywords: Franchising; franchisingová síť; franchisor; ICT - trh informačních a komunikačních technologií; riziko v podnikání; počítač; zákazník; merchandising; marketing; komunikace; Franchising; franchising network; franchisor; ICT – information and communication technologies market; entrepreneurial risk; computer; customer; merchandising; marketing; communication